2020
DOI: 10.1002/pbc.28575
|View full text |Cite
|
Sign up to set email alerts
|

Oral processing speed as a key mechanism in the relationship between neurological risk and adaptive functioning in survivors of pediatric brain tumors

Abstract: Purpose: Brain tumor (BT) survivors are at risk for difficulties with adaptive functioning (AF). Recent work has associated neurological risk with poorer AF outcomes using the Neurological Predictor Scale (NPS), a quantification of neurological risk factors. Survivors also have poorer attention, processing speed, and working memory, which are all important for AF. The current study examined whether these cognitive constructs explain the relationship between the NPS and AF in survivors. Methods: Ninety-five adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Cognitive deficits seen in pediatric brain tumor survivors are often accompanied by difficulties with adaptive functioning (AF) or an individual’s ability to complete activities of daily living (ADLs) and care for themselves (King & Na, 2016; Semmel et al, 2020). AF includes personal functions, such as self-care and mobility, as well as interpersonal functions, such as communication and socialization (Sparrow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive deficits seen in pediatric brain tumor survivors are often accompanied by difficulties with adaptive functioning (AF) or an individual’s ability to complete activities of daily living (ADLs) and care for themselves (King & Na, 2016; Semmel et al, 2020). AF includes personal functions, such as self-care and mobility, as well as interpersonal functions, such as communication and socialization (Sparrow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that commonly observed cognitive deficits in brain tumor survivors are related to and predict AF weaknesses in this population (King, Smith, et al, 2015; Panwala et al, 2019; Semmel et al, 2020). For example, multiple studies have implicated processing speed in AF outcomes in pediatric brain tumor survivors and other populations (Panwala et al, 2019; Semmel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Papazoglou et al demonstrated that attention span predicted the communication score in a cerebellar population of pediatric BT [ 14 ]. Semmel et al found a significant indirect effect in a BT sample between the cognitive predictors of attention span and processing speed (PS), and neurological condition and AF; taken together, however, the neurological risk and PS had the power to explain 39% of the variance in the AF scores [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PS deterioration is mainly caused by a disruption in the white matter, which is extremely important for the diffusion of action potentials, but it is also particularly vulnerable to toxic and physical agents, such as radiation [ 18 , 19 ]. Research on pediatric traumatic brain injury (TBI) patients suggests that PS underlies AF abilities [ 13 , 15 ] and that PS is an important mediator between AF and TBI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation